Metodologi Pengujian dan Validasi Topologi Infrastruktur Jaringan - Naf’an Rasyidi Hartono; Jonathan Aldo Setiawan; Dewi Oktafiani (PT. Hasba Edukasi Mandiri, 2026)
In today's digital era, network infrastructure topology is a crucial component in ensuring the performance and reliability of communication systems. This article discusses a methodology for testing and validating network infrastructure topologies. This research aims to identify and develop efficient procedures for testing and validating various network topologies to ensure optimal stability and performance. The methods used include simulation, performance analysis, and empirical validation through field trials. The results show that the proposed methodology is capable of detecting potential issues and providing recommendations for improvement, thereby improving operational efficiency and network reliability.